Hydro-meteorological Disasters Associated with Tsunamis and Earthquakes - Sagara, Junko (World Bank, Washington, DC, 2013)
Earthquakes and tsunamis increase the risks of hydro-meteorological disasters. After the Great East Japan Earthquake (GEJE), disaster-prevention structures such as coastal and river dikes were quickly rehabilitated. A phased process of rehabilitation work made it possible to address urgent needs for protection against frequently occurring floods and storm surges, while at the same time meeting longer-term targets for protection against mega disasters. The deterioration of levels of protection against hydro-meteorological disasters was quickly assessed after the GEJE in order to identify priority areas for rehabilitation, revise standards for the issuance of warnings, and raise public awareness about the increased risks of hydro-meteorological disasters. This report gives findings; lessons; and recommendations for developing countries.